Measurement of radiant energy using pyroelectric polymer/ceramic composite - Cavalcante, Edinilton Morais [UNESP]; Kanda, Darcy Hiroe Fujii [UNESP]; De Barros Melo, Washington Luiz; De Campos Fuzari Jr., Gilberto; Sakamoto, Walter Katsumi [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Monitoring non-ionizing radiant energy is increasingly demanded for many applications such as automobile, biomedical and security system. Thermal type infrared (IR) sensors can operate at room temperature and pyroelectric materials have high sensitivity and accuracy for that application. Working as thermal transducer pyroelectric sensor converts the non-quantified thermal flux into the output measurable quantity of electrical charge, voltage or current. In the present study the composite made of poly(vinylidene fluoride) - PVDF and lead zirconate titanate (PZT) partially recovered with polyaniline (PAni) conductor polymer has been used as sensor element. The pyroelectric coefficient p(T) was obtained by measuring the pyroelectric reversible current, i.e., measuring the thermally stimulated depolarization current (TSDC) after removing all irreversible contribution to the current such as injected charge during polarization of the sample. To analyze the sensing property of the pyroelectric material, the sensor is irradiated by a high power light source (halogen lamp of 250 W) that is chopped providing a modulated radiation. A device assembled in the laboratory is used to change the light intensity sensor, an aluminum strip having openings with diameters ranging from 1 to 10 mm incremented by one millimeter. The sensor element is assembled between two electrodes while its frontal surface is painted black ink to maximize the light absorption. The signal from the sensor is measured by a Lock-In amplifier model SR530 - Stanford Research Systems. The behavior of the output voltage for an input power at several frequencies for PZT-PAni/PVDF (30/70 vol%) composite follows the inverse power law (1/f) and the linearity can be observed in the frequency range used. © 2013 IEEE.
Keywords: composite; photopyroelectric; PVDF; PZT; radiant energy